Analisis Brand Image dan Loyalitas Merek Operator Seluler pada Mahasiswa Pengguna Telepon Seluler di Fakultas Ekonomi Universitas Tanjungpura Pontianak - B11108156, Vinsensius Dwi Cahyo Nugroho (Jurnal Manajemen Update, 2013)
This study aims to determine the respondents about Attributes, Benefits, Value, Culture, Personality, and the User, who belong to the Variable Brand Image. And Switchers, Habitual buyers, Statisfied Buyer with Switching Costs, Likes The Brand, and Commited Buyer, which belong to the brand loyalty variable of the Economic faculty student of Tanjungpura university. This study uses a form of descriptive research is to describe the phenomena that occur on the brand image and loyalty of mobile phone users in the Economic Faculty Tajungpura University. In sampling, researchers used purposive sampling technique. The sample of 100 people is the whole students of Economic Faculty to analyze the data. The results of each answer is expressed as a percentage, then calculated the average value of variables score that can be interpreted and concluded. The results indicate that respondents are very high on Brand Image variable with an average of 3.43 and Brand Loyalty variable with an average of 3.54. Keywords: Brand Image, Brand Loyalty.